Foreign investment as a factor in Asian Pacific integration - Axel Borrmann; Rolf Jungnickel (Intereconomics, 1992)
The Asian Pacific countries do not only show unparalled growth dynamics, they are also in the process of growing ever closer together. There is already talk of the creation of a new economic bloc. The following article analyses private direct investment in the Asian Pacific area, an element in the economic integration of the region which has been paid little attention until now.
Keywords: 330; Foreign Direct Investment